Makna Lagu '33x' Karya Perunggu dalam Perspektif Teologis - Habibullah, Habibullah; Firdaus, Dadan; Arina, Tazkiyah Marwah; Nursanti, Cita Afiyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Indonesian popular music, particularly within the indie genre, increasingly demonstrates thematic depth that transcends mere entertainment. This study examines the theological meanings embedded in the lyrics of "33X," a song by Perunggu, an Indonesian indie band whose work is rich with spiritual and existential resonance. Employing a qualitative method with a descriptive-analytical approach, this research integrates three analytical frameworks: the hermeneutics of Paul Ricœur and Hans-Georg Gadamer, Charles Sanders Peirce's triadic semiotics, and contextual Islamic theology. The analysis reveals that the lyrics of "33X" contain three layers of meaning — denotative, connotative, and mythological — collectively reflecting a narrative of the modern human spiritual journey amid existential turmoil. Semiotically, the number 33 in the title functions as a symbol of Islamic dhikr, specifically the ritual practice of reciting tasbih, tahmid, and takbir thirty-three times after obligatory prayer. From the perspective of Islamic theology, the song demonstrably embodies values of aqeedah (tauhid rububiyyah), sharia (dhikr as worship), and Sufi ethics (tawakkul, patience, muhasabah, gratitude, istiqamah, and inabah). This study affirms that popular music can serve as an effective medium for conveying spiritual values implicitly.